2004
DOI: 10.1093/humupd/dmh012
|View full text |Cite
|
Sign up to set email alerts
|

Precocious puberty and statural growth

Abstract: Precocious puberty results mostly from the precocious activation of the gonadotropic axis. Although the age limits have recently been discussed, most physicians consider that onset of pubertal development before the age of 8 years in a girl or 9 years in a boy warrants at least a clinical and bone age evaluation by a paediatric endocrinologist. The major concern in precocious puberty is the underlying condition, and central nervous system or gonadal neoplasm have to be formally excluded as a first step in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
156
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 254 publications
(171 citation statements)
references
References 104 publications
5
156
0
10
Order By: Relevance
“…Overall, the majority of studies indicate some beneficial effect of GnRHa treatment on final height in girls when compared with initial height predictions (20). The increment can range from 3 to 10 cm, although realistically, a height gain of 4-6 cm after at least 3-4 years of GnRHa treatment is the estimate for a girl with CPP.…”
Section: Effect Of Gnrha Treatment On Final Heightmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the majority of studies indicate some beneficial effect of GnRHa treatment on final height in girls when compared with initial height predictions (20). The increment can range from 3 to 10 cm, although realistically, a height gain of 4-6 cm after at least 3-4 years of GnRHa treatment is the estimate for a girl with CPP.…”
Section: Effect Of Gnrha Treatment On Final Heightmentioning
confidence: 99%
“…Significant impairment of final height in untreated CPP has dominated the rationale for intervening with GnRH treatment (19). It has been calculated that height loss is of the order of 20 and 12 cm in boys and girls respectively (20). Few studies have evaluated psychosocial outcome following early or precocious puberty, but a long-term Swedish study reported more antisocial behaviour in adolescence and lower academic achievement in adulthood (21).…”
Section: Precocious Puberty: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to treat depends on the age at onset of puberty, pace of pubertal development, estimated adult height, and psychological impact of the premature sexual development (2,3). Treatment is undisputed in rapidly progressive forms, defined on the basis of clinical, radiological, and biochemical criteria (8), for the significant risk of short adult height, while it is not required in patients with nonprogressive or slowly progressive forms who were shown to achieve an adult height within the normal range without treatment (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the widespread use of GnRHa has increasingly demonstrated its favorable effects on statural growth, although the net height gain (HG) associated with the treatment and predictors of long-term outcomes remains debated (2,6,7,8), as no randomized controlled trials (RCTs) have been performed and growth estimation suffers from important methodological limitations, which will be discussed later. Moreover, concerns have been raised on the potential negative effects of treatment on weight and metabolic profile, bone mineral density (BMD), and reproductive function in adulthood (2,3,6).…”
Section: Introductionmentioning
confidence: 99%